2015
DOI: 10.5121/ijcnc.2015.7201
|View full text |Cite
|
Sign up to set email alerts
|

Extending Network Lifetime of Wireless Sensor Networks

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Additionally, the CHs can be assigned different tasks, such as data aggregation, FM, coordinating network reconfiguration or duty cycling, and network maintenance, depending on their resource capacities and network requirements. This case study is based on static SNs and the distributed network construction approach (see references in [9,12,33,[126][127][128][129][130][131][132]), where the SNs locally manage the entire clustering process, and a CH is elected without the entire network's information.…”
Section: Characterization Of Canon Clustering-based Routing Protocols...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the CHs can be assigned different tasks, such as data aggregation, FM, coordinating network reconfiguration or duty cycling, and network maintenance, depending on their resource capacities and network requirements. This case study is based on static SNs and the distributed network construction approach (see references in [9,12,33,[126][127][128][129][130][131][132]), where the SNs locally manage the entire clustering process, and a CH is elected without the entire network's information.…”
Section: Characterization Of Canon Clustering-based Routing Protocols...mentioning
confidence: 99%
“…3. Multihop routing, which is a requirement to attain the desired energy savings and network adaptability in large-scale CA-IoT networks, is asserted to be more energyefficient only in simulation experiments [33,120,121,[123][124][125][128][129][130] but not in realworld implementation [22][23][24]. This imbalance is due to a lack of a comprehensive and reliable theoretical multihop routing framework that is based on the total communication costs of multihop routing.…”
Section: Open Issues and Future Work: Cluster-based Wsn-specific Agri...mentioning
confidence: 99%
“…Additionally, the CHs can be assigned different tasks, such as data aggregation, FM, coordinating network reconfiguration or duty-cycling, and network maintenance, depending on their resource capacities and requirements. This case study is based on static SNs and the distributed network construction approach (see references in [9,12,34,[122][123][124][125][126][127][128]), where the SNs locally manage the entire clustering process, and a CH is elected without the entire network's information.…”
Section: Characterization Of Canon Clustering-based Routing Protocols...mentioning
confidence: 99%
“…Trigeorgis et al (2016) revealed that abusive management referred to the specific performance of leadership practices towards their subordinates in work. Amiri (2015) pointed out that abusive management in the working environment included active abuse or deception. Michel et al (2016) believed that abusive management aimed to control employees through acts of intimidation.…”
Section: The Relationship Between Learning Style and Employees' Profe...mentioning
confidence: 99%